When a loved one is on community supervision: the crime controller strategies used by 'PoPPs' (parents/partners/peers of probationers and parolees). Issue 2 (3rd April 2019) - Schaefer, Lacey; Moir, Emily; Williams, Gemma C.
ABSTRACT: Scholars have called for the incorporation of informal social control agents into the community supervision of offenders, although systematic efforts to do so have been slow to come. This project reports on an initial trial of such a practice. In Triple-S: Social Supports in Supervision, probation and parole staff engage in opportunity-reduction tactics by, in part, recruiting and training members of their clients' social networks who may serve as offender handlers, target guardians, and place managers. The current study analysed interview data from a sample of these PoPPs (parents/partners/peers of probationers and parolees) to uncover the strategies they use in preventing their loved one from reoffending. A thematic analysis revealed eight categories of actions taken by PoPPs: (1) social support, (2) instrumental support, (3) moulding routines and altering environments, (4) reshaping social circles, (5) trigger identification and avoidance, (6) threats, (7) monitoring and intervention, and (8) co-desistance. We further describe the impact of closeness, willingness to intervene, opportunity, and knowledge on the crime control (in)actions of the interview participants, calling for further research on the nature of handling, guarding, and managing behaviours when the relationship between the crime controller and the offender is pre-existing.